What strategies would sheep farmers implement to respond to climate change? A cross-national comparison of sheep farming systems in the Mediterranean - D. Martin-Collado; A. Tenza-Peral; I. Casasús; M. Joy; F. Stark; A. Lurette; A. Mohamed-Brahmi; M. Ameur; A. Aboulnaga; M. Elshafie; S. Lobón (Small Ruminant Research, 2025)

Selenium removal from oil refinery wastewater using nanoscale zero-valent iron particles (nZVI) with and without electrochemical peroxidation - M. E. Hansen; S. Collado; C. Gutiérrez; R. Ortiz; P. Lazo; A. Lazo; H. K. Hansen (International Journal of Environmental Science and Technology, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

Microhabitat impact on Hypnea pseudomusciformis (Rhodophyta) response to environmental changes: Ecological, morphological, and physiological insights - Fabio Nauer; Henrique D. S. Borburema; Alain Duran; Estela M. Plastino; Priscilla B. de Jesus; Mariana C. Oliveira; Ligia Collado-Vides; Mutue T. Fujii (Journal of Applied Phycology, 2025)

Magnetic amyloid-based biocatalyst for the hydrolysis of urea - A. de Athayde Moncorvo Collado; S.B. Socías; F. González-Lizárraga; D. Ploper; E. Vera Pingitore; R.N. Chehín; S. Chaves (Food Chemistry, 2024)

Multiple late‐Pleistocene colonisation events of the Antarctic pearlwort Colobanthus quitensis (Caryophyllaceae) reveal the recent arrival of native Antarctic vascular flora - Elisabeth M. Biersma; Cristian Torres‐Díaz; Marco A. Molina‐Montenegro; Kevin. K. Newsham; Marcela A. Vidal; Gonzalo A. Collado; Ian S. Acuña‐Rodríguez; Gabriel I. Ballesteros; Christian C. Figueroa; William P. Goodall‐Copestake; Marcelo A. Leppe; Marely Cuba‐Díaz; et al. (Journal of Biogeography, 2020)
Aim Antarctica's remote and extreme terrestrial environments are inhabited by only two species of native vascular plants. We assessed genetic connectivity amongst Antarctic and South American populations of one of these species, Colobanthus quitensis , to determine its origin and age in Antarctica. Location Maritime Antarctic, sub‐Antarctic islands, South America. Taxon Antarctic pearlwort Colobanthus quitensis (Caryophyllaceae). Methods Four chloroplast markers and one nuclear marker were sequenced from 270 samples from a latitudinal transect spanning 21–68° S. Phylogeographic, population genetic and molecular dating analyses were used to assess the demographic history of C. quitensis and the age of the species in Antarctica. Results Maritime Antarctic populations consisted of two different haplotype clusters, occupying the northern and southern Maritime Antarctic. Molecular dating analyses suggested C. quitensis to be a young ( Main conclusions. The Maritime Antarctic populations likely derived from two independent, late‐Pleistocene dispersal events. Both clusters shared haplotypes with sub‐Antarctic South Georgia, suggesting higher connectivity across the Southern Ocean than previously thought. The overall findings of multiple colonization events by a vascular plant species to Antarctica, and the recent timing of these events, are of significance with respect to future colonizations of the Antarctic Peninsula by vascular plants, particularly with predicted increases in ice‐free land in this area. This study fills a significant gap in our knowledge of the age of the contemporary Antarctic terrestrial biota. Adding to previous inferences on the other Antarctic vascular plant species (the grass Deschampsia antarctica ), we suggest that both angiosperm species are likely to have arrived on a recent (late‐Pleistocene) time‐scale. While most major groups of Antarctic terrestrial biota include examples of much longer‐term Antarctic persistence, the vascular flora stands out as the first identified terrestrial group that appears to be of recent origin.

Impact of universal access to hepatitis C therapy on HIV-infected patients: implementation of the Spanish national hepatitis C strategy - A. Rivero-Juarez; L. F. Lopez-Cortes; M. Castaño; D. Merino; M. Marquez; M. Mancebo; F. Cuenca-Lopez; P. Jimenez-Aguilar; I. Lopez-Montesinos; S. Lopez-Cardenas; A. Collado; M. A. Lopez-Ruz; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Understanding the simultaneous biodegradation of thiocyanate and salicylic acid by Paracoccus thiocyanatus and Pseudomonas putida - R. G. Combarros; S. Collado; A. Laca; M. Díaz (International Journal of Environmental Science and Technology, 2016)

SAV Communities of Western Biscayne Bay, Miami, Florida, USA: Human and Natural Drivers of Seagrass and Macroalgae Abundance and Distribution Along a Continuous Shoreline - D. Lirman; T. Thyberg; R. Santos; S. Schopmeyer; C. Drury; L. Collado-Vides; S. Bellmund; J. Serafy (Estuaries and Coasts, 2014)

Mapping quantitative trait loci for growth responses to exogenously applied stress induced hormones in wheat - A. M. Castro; M. S. Tacaliti; D. Giménez; E. Tocho; O. Dobrovolskaya; A. Vasicek; M. Collado; J. W. Snape; A. Börner (Euphytica, 2008)